2017
DOI: 10.1093/brain/aww331
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine controls Parkinson’s tremor by inhibiting the cerebellar thalamus

Abstract: Parkinson's resting tremor is related to altered cerebral activity in the basal ganglia and the cerebello-thalamo-cortical circuit. Although Parkinson's disease is characterized by dopamine depletion in the basal ganglia, the dopaminergic basis of resting tremor remains unclear: dopaminergic medication reduces tremor in some patients, but many patients have a dopamine-resistant tremor. Using pharmacological functional magnetic resonance imaging, we test how a dopaminergic intervention influences the cerebral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 60 publications
10
119
1
Order By: Relevance
“…The basal ganglia–receiving portion of the ventral motor thalamus is also innervated by dopaminergic fibers, arising from several dopaminergic cell groups in the midbrain . There appears to be a substantial loss of the thalamic dopaminergic innervation in MPTP‐induced parkinsonism in monkeys, which could be related to the emergence of tremor (see also below) …”
Section: Evolving Topicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The basal ganglia–receiving portion of the ventral motor thalamus is also innervated by dopaminergic fibers, arising from several dopaminergic cell groups in the midbrain . There appears to be a substantial loss of the thalamic dopaminergic innervation in MPTP‐induced parkinsonism in monkeys, which could be related to the emergence of tremor (see also below) …”
Section: Evolving Topicsmentioning
confidence: 99%
“…The pathophysiology of parkinsonian tremor thus likely differs from that of bradykinesia or akinesia (which do not respond to such interventions). Imaging and modeling studies have suggested that dopaminergic denervation of the cerebellar receiving territory of the thalamus may contribute to tremor, and that dopaminergic drugs could act directly in the thalamus in such patients . STN‐DBS also affects cerebellar function, perhaps through the pathways shown in Figure , which may account for some of its antiparkinsonian effects, specifically its effects on parkinsonian tremor .…”
Section: Evolving Topicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the studied cases, 3 fiber components were identified: cerebellar-thalamic-cortical fibers, globus pallidus (Gp)-pedunculopontine fibers, and frontal orbitofrontal cortex-mesencephalic tegmental fibers. Cerebellar thalamic fibers have been implicated in the physiopathology of tremor [4] since a large component enters the nucleus ventralis intermedius (Vim) connecting with the primary motor cortex. Recently it has been described that, with deep brain stimulation (DBS), the achievement of optimum results for tremor control in Vim depends on the proximity of active contacts to the cerebellar fibers ending in the Vim [5].…”
Section: Introductionmentioning
confidence: 99%